Pangnirtung water reservoir: geotechnical aspects - Smith, L. B.; Notenboom, W. G.; Campbell, M.; Cheema, S.; Smyth, T. (Canadian Geotechnical Journal, 1989)
This paper outlines the geotechnical aspects associated with the design and construction of an earthworks water reservoir excavated in ice-rich permafrost in the community of Pangnirtung, N.W.T. The reservoir was constructed by blasting, excavating, and placing frozen silty sand to form the reservoir berms during the winter. The work involved the excavation of about 140 000 m 3 of material. The paper outlines the major geotechnical concerns identified during design and the measures used to deal with them. Observations made during subsequent construction of the reservoir are presented. Key words: permafrost, excavation, construction, water reservoirs, blasting.